2020
DOI: 10.1016/j.ejphar.2020.173430
|View full text |Cite
|
Sign up to set email alerts
|

In silico molecular docking analysis for repurposing therapeutics against multiple proteins from SARS-CoV-2

Abstract: SARS-CoV-2 has devastated the world with its rapid spread and fatality. The researchers across the globe are struggling hard to search a drug to treat this infection. Understanding the time constraint, the best approach is to study clinically approved drugs for control of this deadly pandemic of COVID 19. The repurposing of such drugs can be supported with the study of molecular interactions to enhance the possibility of application. The present work is a molecular docking study of proteins responsible for vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 43 publications
(48 reference statements)
4
55
0
Order By: Relevance
“…Recently, an in silico molecular docking study reported that ER has good binding energies and antiviral effects by its cellular multi-target ability against multiple proteins from SARS-CoV-2, especially the angiotensin converting enzyme 2 (ACE2) [ 95 ]. Moreover, compared to many already known drugs, ER strongly binds to virus replicating proteins such as SARS-CoV-2 helicase which potentially helps recognize RNA: DNA duplex is a unique feature of viruses, and active sites of SARS-CoV-2 spike glycoprotein C chain having 10 amino acids [ 95 ]. Hence, ER appeared to be a novel multi-target molecule for repurposing against SARS-CoV-2.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Recently, an in silico molecular docking study reported that ER has good binding energies and antiviral effects by its cellular multi-target ability against multiple proteins from SARS-CoV-2, especially the angiotensin converting enzyme 2 (ACE2) [ 95 ]. Moreover, compared to many already known drugs, ER strongly binds to virus replicating proteins such as SARS-CoV-2 helicase which potentially helps recognize RNA: DNA duplex is a unique feature of viruses, and active sites of SARS-CoV-2 spike glycoprotein C chain having 10 amino acids [ 95 ]. Hence, ER appeared to be a novel multi-target molecule for repurposing against SARS-CoV-2.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…In a study, two anti-inflammatory drugs, pemirolast and eriodictyol were docked against nsp9 with the resulting binding energy of −6.5 kcal/mol and further suggest their role in inhibiting infection. It has been further reported that retonavir and remdesivir are potential drugs against nsp10, suggesting their ability to inhibit viral transcription [11] . Thus, both proteins can be proved as a potential therapeutic target in combating SARS-CoV-2 pathogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…However, developing a new, effective, and safe vaccine often requires years and poses great risks [ 16 ]. At the same time, a lot of compounds obtained from natural products have been reported for their potential activity in preventing viral entry into cells using in silico analysis and in vitro inhibition experiments [ 17 , 18 ]. For example, curcumin has been reported to modulate the events of SARS-CoV-2 cellular entry and replication [ 19 ].…”
Section: Introductionmentioning
confidence: 99%